Replacement of names for two armoured scale genera (Hemiptera: Coccomorpha: Diaspididae) due to homonymy - Meng, Shitao; Xing, Jichun (Zootaxa, 2022)
Two generic names in the family Diaspididae (Hemiptera: Coccomorpha) were discovered to be homonyms. We propose a replacement name for each of these genera, to bring the taxonomy of scale insects into accordance with the International Code of Zoological Nomenclature (ICZN 1999).